2007
DOI: 10.1108/14777830710778274
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of trends related to hospital solid wastes management in Kuwait

Abstract: Purpose -The purpose of this paper is to determine the amount of different kinds of solid wastes produced, segregated, collected, stored, transported and disposed off in the governmental hospitals of Kuwait. Design/methodology/approach -The research in this paper shows that all governmental hospitals were assessed in a period of six months (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…The amount of HCW generated in the HCEs was positively correlated with the number of beds ( r s = 0.79, p < 0.001). The average waste generation per bed per day in Khulna city has been found to be 0.90 kg ( Table 1 ), which is much lower than that of the developed countries like the United States (4.5 kg bed −1 day −1 ), the United Kingdom (3.3 kg bed −1 day −1 ), and Spain (4.4 kg bed −1 day −1 ) [ 25 , 26 ]. In high-income countries, HCW generation is usually higher than that in the middle and low-income countries [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…The amount of HCW generated in the HCEs was positively correlated with the number of beds ( r s = 0.79, p < 0.001). The average waste generation per bed per day in Khulna city has been found to be 0.90 kg ( Table 1 ), which is much lower than that of the developed countries like the United States (4.5 kg bed −1 day −1 ), the United Kingdom (3.3 kg bed −1 day −1 ), and Spain (4.4 kg bed −1 day −1 ) [ 25 , 26 ]. In high-income countries, HCW generation is usually higher than that in the middle and low-income countries [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, the average quantity of hospital solid waste produced in India ranges from 1.5 to 2.2 kg/day/bed (547–803 kg) (Hemangini and Shah 2000), in Nepal, the total waste generation rate (noninfectious and infectious) is 1.72 kg/bed/day (628 kg) (Pesticide Watch Group 2006; Stankovic et al 2008) indicates that the waste generation rate was 1.92 kg/bed/day (700 kg) (Stankovic et al 2008). The findings in Kuwait indicated that the waste generation rate is markedly higher at between 3.87 and 7.44 kg/bed/day (Alhumoud and Alhumoud 2007).…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…Also in Japan medical waste generation rate is between 1.5 and 3.0 kg/bed day, 4.4 in Spain, 4.01-6.1 kg/bed/day in Jordan and 3.3 kg/bed/day in France. Taghipour and Mosaferi (2009) The USA and Canada 4.3-5.8 Mato and Kassenga (1997) The UK 3.3 US Environmental Protection Agency 2002France 3.3 US Environmental Protection Agency 2002Japan 3-1.5 Kaneko et al (2003) Spain 4.4 Kaneko et al (2003) India 0.5-2 Patil and Pokhrel (2005) and Patil and Shekdar (2001) Turkey 1.92-2.1 Karaka (2002) Kuwait 3.87-7.44 Alhumoud and Alhumoud (2007) Thailand 0.11-0.65 T.C. Report 2001Jordan 4.01-6.1 Bdour et al (2007) As shown in Figure 2, general waste is generated from packaging, food preparations and visitors' activities.…”
Section: Discussionmentioning
confidence: 99%